2022
DOI: 10.1111/jsr.13547
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and violence perpetration: A review of biological and environmental substrates

Abstract: The World Health Organization (WHO) defines violence as "the intentional use of physical force or power, threatened or actual, against oneself, another person, or against a group or community, which either results in or has a high likelihood of resulting in injury, death, psychological harm, maldevelopment, or deprivation" (Krug et al., 2002). The Global Health Observatory of the WHO reported homicide as the third prime cause of death for males aged between 15 and 44 years old; 25% of adults reported a backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…However, in almost all previous studies, aggression or sleep disturbance has been considered a latent variable ( 34 , 40 , 41 ). Aggression and sleep disturbance encompass a dynamic cluster of dimensions and symptoms that interact dynamically to manifest the variable ( 42–44 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in almost all previous studies, aggression or sleep disturbance has been considered a latent variable ( 34 , 40 , 41 ). Aggression and sleep disturbance encompass a dynamic cluster of dimensions and symptoms that interact dynamically to manifest the variable ( 42–44 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of shift work exposes these individuals to poor sleep, high stress (Marquié et al, 2015), and strain on personal relationships in marriages and families (Presser, 2000;Davis et al, 2008;Skoufi et al, 2017), all of which may put one at risk for committing IPV. Existing studies have reported on the relationship between sleep and violence (Paiva and Canas-Simião, 2022); the association between poor sleep and high subjective stress and aggression (Demichelis et al, 2022); occupational violence victimization and sleep problems (Magnavita et al, 2019); hostility as a predictor of sleep quality and quantity (Granö et al, 2008); the correlation between poor sleep and aggression or violence (Kamphuis et al, 2012(Kamphuis et al, , 2014; intensified anger following sleep restriction (Krizan and Hisler, 2019); and how sleep problems contribute to aggression (Krizan and Herlache, 2016). Missing from this research are the effects of misaligned circadian rhythms and socioeconomic status on violence and anger.…”
Section: Introductionmentioning
confidence: 99%